Why Are Indonesians Prone to Support the Islamic State of Iraq And Syria? - Karen Savitri (Universitas Pelita Harapan, 2018)
ISIS declared itself a caliphate, or Islamic state, with Abu Bakar al-Baghdadi as Caliph, claiming himself the successor of Prophet Muhammad and the leader of all Muslims in 2014. They wreak havoc in the Middle East and all the way to Southeast Asia, causing great damages to infrastructure and livelihood of people. ISIS’ violence is all around the media, in the internet, both offline and online news article, and discussed about in social media. Although the information regarding their atrocities is available only one click away, but why are there Indonesians who still do measures to support ISIS? What fuels so much malice towards the non-believer? What motivate them so much to do all these lengths and for what? This study, using constructivism as theory, discuses underlying historical and societal factors to the reason Indonesians are prone to support ISIS. Applying qualitative method, data are collected through interviews and literature study from books and journals. The researcher discussed altogether six push and pull factors, ranging from Indonesia’s historical account, its homegrown radicalism, tendencies of Indonesian Muslims, and millennial generation.BAHASA INDONESIA ABSTRAK: Negara Islam Irak dan Syam, atau lebih dikenal sebagai ISIS, mendeklarasikan dirinya sebagai sebuah khilafah, atau negara Islam, dengan Abu Bakar Al-Baghdadi sebagai Khalifah atau pemimpin atas segala umat Muslim, pada tahun 2014. Dalam aksinya, mereka membunuh banyak orang, merugikan harta benda, serta membuat kerusakan infrastruktur dari wilayah kekuasaannya di Timur Tengah sampai dengan Asia Tenggara. Kabar kekerasan ISIS terdengar melalui media massa, dari internet, dalam artikel berita, dan didiskusikan di media sosial. Namun, dengan segala informasi mengenai kekejaman ISIS, mengapa masih ada orang Indonesia yang mendukung ISIS? Apa yang membuat mereka membenci orang-orang kafir? Apa yang memotivasi mereka untuk berjuang demi ISIS, bahkan sampai rela untuk kehilangan nyawa? Penelitian ini, dengan mengaplikasikan teori konstruktivisme, mendiskusikan kisah sejarah Indonesia dan faktor sosial yang mendasari alasan orang Indonesia mendukung ISIS. Dengan metode penelitian kualitatif, data dikumpulkan melalui interview dan studi literatur dari buku dan artikel penelitian. Peneliti mendiskusikan total 6 (enam) faktor pendorong dan penarik, mulai dari kisah sejarah, radikalisme di Tanah Air, kecendrungan orang Muslim di Indonesia, dan generasi milenial.